2014
DOI: 10.1115/1.4025952
|View full text |Cite
|
Sign up to set email alerts
|

End Wall Loss Reduction of High Lift Low Pressure Turbine Airfoils Using Profile Contouring—Part II: Validation

Abstract: The hypothesis, posed in Part I, that excessive end wall loss of high lift low pressure turbine (LPT) airfoils is due to the influence of high stagger angles on the end wall pressure distribution and not front loading is evaluated in a linear cascade at Re = 100,000 using both experimental and computational studies. A nominally high lift and high stagger angle front-loaded profile (L2F) with aspect ratio 3.5 is contoured at the end wall to reduce the stagger angle while maintaining the front loading. The conto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Numerous planes of Q contours throughout the passage of the cascade for both the baseline flow case and EF profile were compared in Refs. [11,22]. Both studies found a decrease in inlet boundary layer separation and a weaker PV that had shifted forward in the passage when the EF profile was used, in agreement with the present oil flow visualization.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Numerous planes of Q contours throughout the passage of the cascade for both the baseline flow case and EF profile were compared in Refs. [11,22]. Both studies found a decrease in inlet boundary layer separation and a weaker PV that had shifted forward in the passage when the EF profile was used, in agreement with the present oil flow visualization.…”
Section: Methodssupporting
confidence: 89%
“…While the basic mean secondary flow model has been known for years, see for example the review paper of Langston [4], there is on-going computational and experimental research by several groups working toward better physical understanding and modeling of high-lift LPT aerodynamics. Various loss reduction strategies for the secondary flow region have been developed including passive techniques such as endwall surface shaping or contouring [5][6][7], profile contouring near the blade/endwall junction [8][9][10][11][12], and endwall fences [13,14]. These approaches are typically optimized for a single flow condition.…”
Section: Introductionmentioning
confidence: 99%
“…The boundary layer control of low-pressure turbine has two control methods, active control and passive control. Passive control methods mainly include: leading edge variants (Sangston, Little et al 2014), passive vortex generators , Zhang, Vera et al 2005, grooves , etc. The disadvantages of passive control methods are unable to adapt to other variable working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the secondary flow and the associated losses, various passive and active flow control applications in turbines are discussed in the literature [12]. Passive flow control initiatives, non-axisymmetric endwall contouring [13], leading-edge fillets/bulbs [14], a boundary layer endwall fence [15], tubercles [16], undulated blade [17], etc., have all been pursued with varying degrees of success, however, they have the disadvantage of being permanent; thus, they produce an unwanted penalty loss at different operating conditions. As the active flow control initiatives, air suction [18], steady jet blowing [19], and pulsed jet blowing [20], have been demonstrated for secondary flow reduction.…”
Section: Introductionmentioning
confidence: 99%